2
$\begingroup$

My textbook says that

Given $$\vec{u}=\langle a_1,a_2,a_3\rangle,\space \vec{v}=\langle b_1,b_2,b_3\rangle$$ We need to find vector $\vec{w}=\langle x,y,z\rangle$ that is perpendicular to both vectors $\vec{u}$ and $\vec{v}$. Then $\vec{u}\cdot\vec{w}=0$ and $\vec{v}\cdot\vec{w}=0$. Then we have the following simultaneous equations. $$\begin{cases}a_1x+a_2y+a_3z=0\\b_1x+b_2y+b_3z=0\end{cases}$$ Then by solving we can reach the final solution $$\vec{w}=\langle a_2b_3-a_3b_2,a_3b_1-a_1b_3,a_1b_2-a_2b_1\rangle$$

Now, I wonder how did he reach the final result with just two simultaneous equations involving 3 variables

$\endgroup$
  • $\begingroup$ He probably also used the relation between the norms of the vectors. $\endgroup$ – NDewolf May 6 '18 at 9:28
0
$\begingroup$

The system of equations has infinitely many solutions as one should expect, since the orthogonal space $<\vec{u},\vec{v}>^{\perp}$ is one dimensional, the cross product is the unique vector in this orthogonal complement that has as norm $||\vec{u}||||\vec{v}||\sin(\angle(\vec{u},\vec{v}))$ which is the area of the parallelogram spanned by these two vectors and that fullfills the right hand rule. This makes sense for example when desribing a torque:https://en.wikipedia.org/wiki/Torque

$\endgroup$
2
$\begingroup$

You can move the $z$ terms to the right side and solve for $x$ and $y$ in terms of $z$: $$\begin{cases}a_1x+a_2y+a_3z=0\\b_1x+b_2y+b_3z=0\end{cases} \implies \begin{cases}a_1x+a_2y=-a_3z\\b_1x+b_2y=-b_3z\end{cases} \\\implies \begin{pmatrix} a_1&a_2\\b_1&b_2 \end{pmatrix} \begin{pmatrix} x\\y \end{pmatrix} =-\begin{pmatrix} a_3\\b_3 \end{pmatrix}z.$$ If $a_1 b_2 -a_2 b_1 \neq 0$, then $$\begin{align} \begin{pmatrix} x\\y \end{pmatrix} &=-\frac{1}{a_1 b_2 -a_2 b_1} \begin{pmatrix} b_2&-a_2\\-b_1&a_1 \end{pmatrix} \begin{pmatrix} a_3\\b_3 \end{pmatrix}z\\ &=\frac{1}{a_1 b_2 -a_2 b_1} \begin{pmatrix} a_2b_3-a_3b_2\\ a_3b_1-a_1b_3 \end{pmatrix} z.\\ \end{align}.$$ The system of equations has then an infinite number of solutions, namely one for every choice of $z$. Choosing $z=a_1 b_2 -a_2 b_1$ gives $x=a_2b_3-a_3b_2$ and $y=a_3b_1-a_1b_3$.

$\endgroup$
1
$\begingroup$

The solution you write is a particular solution of the system of equation written in your post. Any vector colinear to $\vec{w}$ will also be a solution of the equation system (if $\vec{v}$ is a solution of the system then $\lambda \vec{v}$ is a solution as well).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.